2015
DOI: 10.1177/1933719114537715
|View full text |Cite|
|
Sign up to set email alerts
|

Uterine Infusion With Bone Marrow Mesenchymal Stem Cells Improves Endometrium Thickness in a Rat Model of Thin Endometrium

Abstract: Bone marrow mesenchymal stem cells (BMSCs) show multidirectional differentiation and possess immunoregulatory properties. Although transplantation of BMSCs has a therapeutic effect on many diseases, it is unclear whether BMSC transplantation can be used as a therapy for a thin endometrium. To explore whether transplantation of BMSCs directly into the uterine cavity can improve endometrium thickness, a thin endometrium rat model was established by infusing ethanol into the uterine cavity. In all, 48 rats with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 30 publications
4
71
1
4
Order By: Relevance
“…In the present study, we show that human SPIOs-labeled CD133 þ cells engrafted around blood vessels, a location that has previously been described as the endometrial stem cell niche (5,7,16,36). The signals driving the migration and homing of endothelial progenitor cells to injured endothelium sites or extravascular tissue are largely unknown (37).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the present study, we show that human SPIOs-labeled CD133 þ cells engrafted around blood vessels, a location that has previously been described as the endometrial stem cell niche (5,7,16,36). The signals driving the migration and homing of endothelial progenitor cells to injured endothelium sites or extravascular tissue are largely unknown (37).…”
Section: Discussionmentioning
confidence: 78%
“…There is additional evidence that murine bone marrow mesenchymal stem cells contribute to endometrial restoration in rodents (14)(15)(16)27), and bone marrow injection has been shown to promote endometrial regeneration and restore fertility in an AS model (15,17). In this work, our aim is to demonstrate that human CD133 þ BMDSC injection by intrauterine or systemic delivery could promote endometrial proliferation and the resulting reduction of fibrosis in a murine model of AS.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A recent study by Zhao et al showed a positive effect of bone marrow mesenchymal stem cells treatment on a rat model with thin endometrium. 23 Moreover, a collagen scaffold loaded with …”
Section: Discussionmentioning
confidence: 99%
“…32 At the clinical level several studies suggest the possible application of stem cell therapies for Asherman syndrome, which causes endometrial destruction. [33][34][35][36] Our group is also performing similar work, which has demonstrated the beneficial effect of BMDCs and their ability to home and to colonize murine endometrium, where they engraft mainly around the vascular space (unpublished data). Four months later endometrial thickness, morphology, and vascularity improved and a pregnancy was successfully obtained after in vitro fertilization treatment.…”
Section: Exogenous Sources Of Endometrial Ascsmentioning
confidence: 92%